2018
DOI: 10.1108/ijse-04-2017-0167
|View full text |Cite
|
Sign up to set email alerts
|

Does poverty lead to crime? Evidence from the United States of America

Abstract: Purpose Economic hardship and crime is always a debatable issue in the political economy literature. Some authors define poverty leads to crime some are completely opposite. The purpose of this paper is to find out the impact of poverty on crime in the USA. Design/methodology/approach Using time series data of USA over the period from 1965 to 2016, this study applies autoregressive distributed lag approach to identify the effect of poverty on crime. Findings The outcomes confirm a positive co-integrating r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 45 publications
0
16
0
1
Order By: Relevance
“…For example, there is an ongoing research debate on whether higher levels of violence in the American South compared with the American Northwhich concur with regional bullying trends that find more bullying in schools in the American South than schools in the American North (McCann 2018)-are due to cultural differences, or due to poverty and socioeconomic inequality (Lee et al 2007). However, these theories are not mutually exclusive and consistent with the fact that lower SES neighborhoods tend to have higher crime rates (Imran et al 2018) and that lower SES adolescents more strongly self-report aggression-and bullying-related mindsets, such as lower feelings of a sense of purpose and academic status insecurity (Dietrich and Zimmermann 2019).…”
Section: The Link Between Disadvantaged Family Background and Bullyinmentioning
confidence: 93%
“…For example, there is an ongoing research debate on whether higher levels of violence in the American South compared with the American Northwhich concur with regional bullying trends that find more bullying in schools in the American South than schools in the American North (McCann 2018)-are due to cultural differences, or due to poverty and socioeconomic inequality (Lee et al 2007). However, these theories are not mutually exclusive and consistent with the fact that lower SES neighborhoods tend to have higher crime rates (Imran et al 2018) and that lower SES adolescents more strongly self-report aggression-and bullying-related mindsets, such as lower feelings of a sense of purpose and academic status insecurity (Dietrich and Zimmermann 2019).…”
Section: The Link Between Disadvantaged Family Background and Bullyinmentioning
confidence: 93%
“…There is a high need to increase social spending on education and health infrastructure in order to combat POV and crime rates in a given country. Imran et al (2018) considered a time series data of US for a period of 1965-2016 and concluded that incidence of POV increases the intensity of property crime in a given country, while other controlling factors including country's PCI and unemployment rate are not significantly associated with property crime in a country. The study concludes that property crime should be restricted by strong legislative and regulatory measures, judicious income distribution, and increasing minimum wage rate, which altogether would be helpful for the poor to reap economic benefits from PPG reforms in a country.…”
mentioning
confidence: 99%
“…The idea behind this finding is that economic instability leads to more crimes, particularly crimes against property. Imran et al (2018) found a statistically significant relationship between poverty and crime against patrimony in the US between 1965 and 2016. In India, there is a causal link between crime and poverty attributed to trade and climate change.…”
Section: The Reduction Of Povertymentioning
confidence: 96%